Evaluation of forced oscilometry technique's parameters in severe obstructive sleep apnea patients without breathing disorder - Besharat Rahimi; Maryam Edalatifard; Khosro Sadeghniiat Haghighi; Hossein Kazemzadeh (Journal of Family Medicine and Primary Care, 2020)
Background: Forced oscillometry technique (FOT) is a noninvasive technique that measures reactance and resistance capacity of the lung and is a practical and less time-consuming technique for respiratory effort assessment. Recently, FOT has provided beneficial data regarding the screening of the patients with obstructive sleep apnea (OSA) and assessing the disease progression. The current study aimed to evaluate the correlation of FOT parameters with severity of the apnea-hypnea index (AHI). Methods: In the current case series, all patients who had a body mass index ranging between 30 and 35, suffering severe OSA with AHI of more than 30 times per hour, were enrolled. Patients underwent FOT before treatment to measure the following FOT parameters: Respiratory resistance at 5 and 20 Hz (R5 and R20, respectively), resistance difference between R5 and R20, reactance at 5 Hz (X5), and resonant frequency (Fres). Results: In the current study, 22 patients were enrolled; whereas 12 (54.5%) were male and 10 (45.5%) were female with a mean age of 5.27 ± 4.34. A statistically significant, strong negative correlation was observed between Fres and AHI, during Pearson correlation analysis (r (20) =0.59, P < 0.0001). However, the relationship between the AHI and R5, R20, R5-R20 and X5 was not statistically significant. Similarly, the multiple regression model showed that, only Fres variable added statistically significantly to the prediction, P = 0.01. Conclusion: FOT is a useful tool in evaluation of AHI severity in patients suffering OSA and can be used as a diagnostic material in monitoring and management of these patients.